Climate Change, Mitigation, and Developing Country Growth - Spence, Michael (World Bank, Washington, DC, 2017)
This paper deals with global mitigation strategy. More specifically the main purpose is to address the question of whether growth in the developing world is consistent with long?run climate change objectives. The first part of this paper lays out time paths for emissions for countries in various categories. These paths are consistent with countries' growth objectives, incomes, and capacity to absorb mitigation costs. The intent is to show that while global emissions are likely to remain flat or even to rise as a result of the combined effect of mitigation undertaken by advanced countries and growth in the developing world, eventually reasonably safe global per capita levels can be reached on a 50?year time horizon. The second part of this paper discusses countries' roles in relation to different categories and mechanisms that will support the achievement of safe emissions paths. These mechanisms create incentives and deal with the absorption of costs. In particular, the paper argues that a carbon credit trading system in the advanced countries, combined with an effective cross?border mechanism and a 'graduation' criterion for developing countries to join the advanced group, will create strong incentives, achieve a fair pattern of cost absorption, and support the dynamics described in part one. One point emerges clearly: the cross?border mechanism (or international offsets) is essential in dealing with both the efficiency and the cost absorption and equity challenges of a global mitigation strategy.